Irinotecan and oxaliplatin: an overview of the novel chemotherapeutic options for the treatment of advanced colorectal cancer - Grivicich,I. (2001)
Colorectal cancer is one of the most frequent malignancies in humans and an important cause of cancer death. Metastatic colorectal cancer remains incurable with available systemic therapeutic options. The most active cytotoxic drug against this malignancy, the antimetabolite 5-fluorouracil, was developed more than forty years ago, and as a single agent produces responses in only 10 to 15% of patients which in general last less than one year. Efforts to ameliorate these poor results resulted in the 5-fluorouracil/leucovorin combination, which enhances response rates about two-fold, without, however, significantly improving survival rates. The recent emergence of a handful of new 5-fluorouracil analogues and folate antagonists, as well as the topoisomerase I inhibitor irinotecan, and the third-generation platinum compound oxaliplatin, is likely to alter this gloomy scenario. These agents are at least as effective as 5-fluorouracil in patients with advanced colorectal carcinoma, both untreated and previously treated with 5-fluorouracil-based regimens. This has led to the approval of irinotecan as second-line treatment for 5-fluorouracil-refractory disease, while the use of oxaliplatin has been suggested for patients having a defective 5-fluorouracil catabolism. Recently, FDA approved the combination of irinotecan with 5-fluorouracil and leucovorin for first-line treatment of advanced colon cancer. Based on the synergistic preclinical antitumor effects of some of these agents, their meaningful single-agent activity, distinct mechanisms of cytotoxicity and resistance, and only partially overlapping toxicity profiles, effective combination regimens are now being developed, which are likely to lead to a new, more hopeful era for patients suffering from advanced colorectal carcinoma.